Method for detecting 2D grapevine winter pruning location based on thinning algorithm and Lightweight Convolutional Neural Network - Yang, Qinghua; Yuan, Yuhao; Chen, Yiqin; Xun, Yi (International Journal of Agricultural and Biological Engineering, 2022)
In viticulture, there is an increasing demand for automatic winter grapevine pruning devices, for which detection of pruning location in vineyard images is a necessary task, susceptible to being automated through the use of computer vision methods. In this study, a novel 2D grapevine winter pruning location detection method was proposed for automatic winter pruning with a Y-shaped cultivation system. The method can be divided into the following four steps. First, the vineyard image was segmented by the threshold two times Red minus Green minus Blue (2R−G−B) channel and S channel; Second, extract the grapevine skeleton by Improved Enhanced Parallel Thinning Algorithm (IEPTA); Third, find the structure of each grapevine by judging the angle and distance relationship between branches; Fourth, obtain the bounding boxes from these grapevines, then pre-trained MobileNetV3_small×0.75 was utilized to classify each bounding box and finally find the pruning location. According to the detection experiment result, the method of this study achieved a precision of 98.8% and a recall of 92.3% for bud detection, an accuracy of 83.4% for pruning location detection, and a total time of 0.423 s. Therefore, the results indicated that the proposed 2D pruning location detection method had decent robustness as well as high precision that could guide automatic devices to winter prune efficiently. Keywords: grapevine winter pruning, Lightweight Convolutional Neural Network, thinning algorithm, detection method DOI: 10.25165/j.ijabe.20221503.6750 Citation: Yang Q H, Yuan Y H, Chen Y Q, Xun Y. Method for detecting 2D grapevine winter pruning location based on thinning algorithm and Lightweight Convolutional Neural Network. Int J Agric & Biol Eng, 2022; 15(3): 177–183.